Causal SEO Experimentation in Applied Digital Marketing: Quasi-Experimental Methods for Measuring Organic Impact Under Confounding - Irfan Nurdiansyah Irfan Nurdiansyah (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article presents a causal experimentation framework for SEO that is designed to be practical under real-world constraints where classical randomized controlled trials are often infeasible, and it formalizes quasi-experimental approaches that can quantify organic impact using page-group level designs, matched controls, and time-series counterfactual modeling. The methodology integrates difference-in-differences, synthetic control, and Bayesian structural time series approaches within an operational workflow that begins with hypothesis and mechanism specification, continues through intervention scoping and eligibility gating, and ends with robustness checks that explicitly test sensitivity to indexation delays, lag structure, and spillover effects across query and page clusters. A generic case design is used to demonstrate how the framework can estimate the causal lift of three common SEO interventions, namely title and snippet rewrites, internal linking reinforcement, and performance improvements, while controlling for temporal demand changes and segment-level volatility. Results show that the largest source of measurement error is not statistical noise but design leakage, particularly when treatment and control groups share overlapping query intent or when interventions cause redistribution of impressions within a site rather than net growth, and the study therefore emphasizes guardrails including intent isolation, contamination monitoring, and pre-registered success metrics. The article contributes to Techne’s applied technology scope by translating SEO evaluation into an engineering measurement problem, providing implementable causal designs, and offering decision-ready reporting templates that reduce false positives and improve the reliability of organic optimization programs.